FURTHER STUDIES ON THE PLANKTON OF THE INSHORE WATERS OFF MANDAPAM - Raghu Prasad, R (Indian Journal of Fisheries, 2016)
In an earUer paper the author (Prasad, 1954 a) described the characteristics of marine plankton at an inshore station in the Gulf of Mannar based on regular plankton samples collected from a single station. Mandapam is located on a narrow strip of land lying east-west, with the Palk Bay to the north and the Gulf of Mannar to the south.